Determinants of Fire Impact in the Brazilian Biomes - Oliveira, Ubirajara; Soares-Filho, Britaldo; Bustamante, Mercedes; Gomes, Leticia; Ometto, Jean P.; Rajão, Raoni (Frontiers in Forests and Global Change, 2022)
More and more, wildfires are raging in large parts of the world due to a warmer climate and land-use changes. In Brazil, the deterioration of the public environmental policies has further aggravated wildfires with widespread impacts across the country. Here, we investigated the determinants of the impact of fire in the Brazilian biomes using a dataset of burned areas between 2001 and 2019 to simulate its future impact under policy and climate scenarios. We began by deriving a fire impact index using a principal component analysis (PCA) comprising the variables: 1.fire intensity, 2.fire recurrence, 3.burned area size, 4.mean time interval between successive fires, 5.predominance of fires in the dry season. We considered as High Impact Fires (HIF) those areas whose first PCA-axis values were above the 90th percentile. HIF occurred in the Amazon, Cerrado and Pantanal but not in other biomes. As the main drivers of HIF, our spatial autoregressive models (Amazonia R2=0.66, Pantanal R2=0.86, Cerrado R2=0.79) indicated the climate (Amazon=25%, Pantanal=53%, Cerrado=56%) together with land-use change (Amazon=75%, Pantanal=25%, Cerrado=38%). Most HIF occurred in native vegetation remnants (Amazon=55%, Pantanal=86%, Cerrado=94%). Only in Pantanal fuel loads was a major determinant of HIF (22%). In the Cerrado, it only accounted for 4% of explanation and in the Amazon, it was not even significant. Over the analyzed period, HIF imposed a loss of 23% on the NDVI response of the native vegetation in the Amazon, 19% in the Cerrado and 16% in the Pantanal, indicating physiological stress. Simulations of future climate and land-use change pointed to a dramatic increase in HIF by 2050. Under a best-case scenario (RCP4.5 and strong environmental governance), HIF in the Cerrado would expand from the current 3% of the biome to 15%, from 7% to 8% in the Pantanal and from 0.7% to 1.2% in the Amazon. In addition, the impact of fire would intensify in 95% of the Cerrado, 97% of the Amazon and 74% of the Pantanal. Effective public and private policies will be vital to mitigate the growing threat of HIF. In this sense, our spatially explicit models can help direct prevention and firefighting programs.